TMIC-22. EXOSOMAL NON-CODING RNAS MEDIATE THE CROSS-TALK OF BRAIN METASTASIS CANCER STEM CELLS AND MICROGLIA. (5th November 2018) - Cazacu, Simona; Jiang, Wei; Xiang, Cunli; Hammoud, Zane; Scarpace, Lisa; Kalkanis, Steven; Brodie, Chaya
Abstract: Brain metastases are the most common secondary brain tumors in adults. Despite their high frequency and patient poor prognosis, very little research has been performed on lung tumor brain metastases, mainly due to the lack of appropriate experimental models. In this study, we isolated cancer stem cells (CSCs) from fresh specimens of lung tumor brain metastases. The CSCs were analyzed for sphere formation and limiting dilution analyses, stemness markers, ability to generate xenografts and for their interaction with microglia cells. We found that CSCs derived from brain metastases had a high sphere forming capacity and self-renewal ability comparable to that of glioma stem cells. The CSCs expressed the stemness markers, CD133, Sox2, Klf4, Aldh2a, CD44 and the lung tumor markers, cytokeratin 7, and CD166. Transplantation of the CSCs or organoids generated from the brain metastases formed xenografts that recapitulated the parental tumors. These xenografts were infiltrated by a large number of amoeboid microglia that expressed high levels of M2 markers. Using co-culture experiments, we further found that CSCs derived from brain metastasis induced the polarization of microglia to the M2 phenotype via secreted exosomes. Similarly, M2 micrglia cells increased the self-renewal and stemness of the CSCs. RNA seq analysis identified specific miRNAs and lncRNAs that were associated with the CSC-microglia interactions. Using specific reporters, antagomiRs and CRISPR/Cas9 we demonstrated that miR-21, miR-1246 and the lncRNA TALNEC2 played a major role in the M2 polarization of microglia cells both in vitro and in vivo. In conclusion, we generated CSCs and organoids from lung tumor-derived brain metastases and identified potential therapeutic targets for these tumors. The established CSCs can serve as valuable in vitro and in vivo models for analyzing mechanisms involved in brain metastasis, for studying the tumor-microenvironment interactions and for personalized high throughput screening of new and repurposed drugs.